2006
DOI: 10.2332/allergolint.55.387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salmeterol Xinafoate and Fluticasone Propionate on Immunological Activation of Human Cultured Mast Cells

Abstract: The immunological release of chemical mediators (histamine, LT, PGD(2)) from HCMC was inhibited by SX but not by FP. SX and FP inhibited the production of GM-CSF by HCMC and both drug showed synergistic inhibition in the production of GM-CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…However, in vitro studies have suggested that there are dose-dependent effects of fluticasone on the inhibition of IL-8 and other mediators released from various types of cells, including airway epithelial cells [24], smooth muscle cells [25] and fibroblasts [26]. A synergistic effect of SFP on the inhibition of mediator release has also been demonstrated [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro studies have suggested that there are dose-dependent effects of fluticasone on the inhibition of IL-8 and other mediators released from various types of cells, including airway epithelial cells [24], smooth muscle cells [25] and fibroblasts [26]. A synergistic effect of SFP on the inhibition of mediator release has also been demonstrated [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that the rapid nongenomic effect of GCs functions by preventing the airway constriction reaction and inhibiting degranulation of mast cells in an allergic asthmatic model of guinea pigs (Zhou et al, 2008(Zhou et al, , 2003. In addition, GCs also have a potent inhibitory effect on cytokine release from a human mast cell line (Lippert et al, 1996;Akabane et al, 2006). It has been established that GCs affect β 2 -receptor-mediated signal transduction (Collins et al, 1988); the β 2 -receptor gene is responsive to transcriptional upregulation in response to GC exposure (Baraniuk et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…Both short-acting β 2 -agonists, such as salbutamol and terbutaline, and longer-acting agonists such as salmeterol and formoterol, have also been demonstrated to inhibit the FcεRI-mediated degranulation and the release of PGD 2 , and LTs from human mast cells [96][97][98]. Moreover, β 2 agonists have been shown to inhibit IgE-dependent cytokine production such as GM-CSF and TNF-α in these cells [98,99]. As with other GPCRs that downregulate FcεRI-mediated degranulation, the inhibitory properties of β 2 agonists are mediated by the G sdependent activation of adenylate cyclase, and subsequent increase in intracellular cAMP [100].…”
Section: -Adrenergic Agonistsmentioning
confidence: 99%
“…β 2 -adrenoceptor agonists are used as bronchodilators in the therapeutic management of asthma [95,96]. Both short-acting β 2 -agonists, such as salbutamol and terbutaline, and longer-acting agonists such as salmeterol and formoterol, have also been demonstrated to inhibit the FcεRI-mediated degranulation and the release of PGD 2 , and LTs from human mast cells [96][97][98]. Moreover, β 2 agonists have been shown to inhibit IgE-dependent cytokine production such as GM-CSF and TNF-α in these cells [98,99].…”
mentioning
confidence: 99%